Biosorption of copper ions from aqueous solution using Kappaphycus striatum - N K, Mun; Nadiah, Mokhtar; N F, Shoparwe; H, Shukor (IOP Science, 2021)
Abstract. Biosorption is an eco-friendly alternative technology for the removal of heavy metals from industrial waste and effluents using low-cost and effective biosorbent. Abundant of natural materials like agricultural biomass, industrial waste, and microbial biomass can be used as a promising biosorbent. In the present study, red algae Kappaphycus striatum biomass will be used for the adsorption of copper ions in aqueous solution. The free (non-immobilized) and immobilized form of red algae Kappaphycus striatum biomass and biosorption rate were investigated for the adsorption process. The maximum biosorption of copper ions was achieved when immobilized form of algae biomass were used at the condition pH of 5, biomass dosage, 0.25 g/L, contact time of 90 minutes, and at the temperature of 50 ℃ with a 65.8% of removal. The experiment data for biosorption rate with time also was used to evaluated two kinetic models (pseudo-first-order and pseudo-second-order) and two isotherm models (Langmuir and Freundlich). The results reveal that metallic ions biosorption on the immobilized Kappaphycus striatum followed the pseudo-second-order kinetic model with a R2=0.9996 and Langmuir isotherm model with a R2=0.9999. The present work shows that the red algae of Kappaphycus striatum as a potential biosorbent for the removal of heavy metal ions from aqueous solution